DAMPAK PEMBANGUNAN MANUSIA, KEMISKINAN DAN PENGANGGURAN TERHADAP PERTUMBUHAN EKONOMI TAHUN 2017-2021 DI JAWA TIMUR - Wisdawan, Kukuh Tri; Pratomo, Devanto Shasta (Journal of Development Economic and Social Studies, 2024)
Economic growth is the development of economic activities that cause changes in the goods and services produced in everyday life. The level of economic growth in a region shows the level of change in the economic welfare of its people. East Java Province is one of the contributors to economic growth that is comparable to the national level. The amount of economic growth in a region can be influenced by several factors, namely: human development, poverty and unemployment. This research aims to identify and analyze the influence of human development, poverty levels and unemployment levels on economic growth in East Java Province. Based on the objectives to be achieved by the author, the type of research that will be used is panel data regression in the 2017-2021 time period. The research results show that human development has a positive and significant effect on economic growth, the poverty level has a positive and significant effect on economic growth, while the unemployment rate has a negative and insignificant effect on economic growth. However, human development, poverty and unemployment together have an influence on economic growth.